Individual differences in affect in response to physical activity - Takahashi, Shinji; Sakairi, Yosuke; Grove, Philip M. (Frontiers in Psychology, 2025)
IntroductionA single bout of physical activity can benefit one’s psychological state, increasing positive affect. Individual differences in these feelings are known to correlate with mental health; however, individual differences in response to physical activity are unclear. This study aimed to quantitatively evaluate individual differences in affect in response to acute physical activities. Quantifying those individual differences implicitly assumed in previous studies would facilitate understanding the relationship between physical activity adherence and mental health.MethodsThe dataset comprised valence (pleasant-unpleasant) and arousal (active-inactive) measurements taken before and after two types of physical activities (running and badminton) with a crossover design. Valence and arousal were analyzed using a mixed model. Then, the intraclass correlation coefficients (ICCs) for valence and arousal, which are the ratio of the variance components of individual differences and the sum of total variance components, were calculated. Information processing in cognitive functions was also analyzed and compared variance components among valence, arousal, and information processing to comprehensively evaluate individual differences in valence and arousal in response to physical activity.Results and discussionThe results showed that individual differences in valence and arousal in response to physical activity were significant variance components, whereas the variance component in information processing was not significant. The ICCs for valence, arousal, and information processing were 0.603 (95% confidence interval [95%CI]: 0.430–0.769), 0.349 (95%CI: 0.202–0.512), and 0.171 (95% CI: 0.164–0.217), respectively, demonstrating that the ICC for valence is significantly more pronounced than that for information processing. These findings indicate that the effects of physical activity on affect vary among individuals, particularly regarding changes in valence. Considering individual differences is essential when tailoring physical activity treatments for health.